Is abdominal wall contraction important for normal voiding in the female rat? - Smith, Phillip P (BioMed Central, 2007)
BACKGROUND: Normal voiding behavior in urethane-anesthetized rats includes contraction of the abdominal wall striated muscle, similar to the visceromotor response (VMR) to noxious bladder distension. Normal rat voiding requires pulsatile release of urine from a pressurized bladder. The abdominal wall contraction accompanying urine flow may provide a necessary pressure increment for normal efficient pulsatile voiding. This study aimed to evaluate the occurrence and necessity of the voiding-associated abdominal wall activity in urethane-anesthetized female rats METHODS: A free-voiding model was designed to allow assessment of abdominal wall activity during voiding resulting from physiologic bladder filling, in the absence of bladder or urethral instrumentation. Physiologic diuresis was promoted by rapid intravascular hydration. Intercontraction interval (ICI), voided volumes and EMG activity of the rectus abdominis were quantified. The contribution of abdominal wall contraction to voiding was eliminated in a second group of rats by injecting botulinum-A (BTX, 5 U) into each rectus abdominis to induce local paralysis. Uroflow parameters were compared between intact free-voiding and BTX-prepared animals. RESULTS: Abdominal wall response is present in free voiding. BTX preparation eliminated the voiding-associated EMG activity. Average per-void volume decreased from 1.8 ml to 1.1 ml (p < 0.05), and reduced average flow from 0.17 ml/sec to 0.11 ml/sec (p < 0.05). Intercontraction interval (ICI) was not changed by BTX pretreatment. CONCLUSION: The voiding-associated abdominal wall response is a necessary component of normal voiding in urethane anesthetized female rats. As the proximal urethra may be the origin of the afferent signaling which results in the abdominal wall response, the importance of the bladder pressure increment due to this response may be in maintaining a normal duration intermittent pulsatile high frequency oscillatory (IPHFO)/flow phase and thus efficient voiding. We propose the term Voiding-associated Abdominal Response (VAR) for the physiologic voiding-associated EMG/abdominal wall response, to distinguish it from the visceromotor response (VMR) to noxious bladder distension.